The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00262-017-1997-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated myeloid cells as guiding forces of cancer cell stemness

Abstract: Due to their ability to differentiate into various cell types and to support tissue regeneration, stem cells simultaneously became the holy grail of regenerative medicine and the evil obstacle in cancer therapy. Several studies have investigated niche-related conditions that favor stemness properties and increasingly emphasized their association with an inflammatory environment. Tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) are major orchestrators of cancer-related inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…[12,31] The immunosuppressive roles of MDSCs are relatively well-understood in tumors. [12,31,34] It has been reported that MDSC enhances stem-like qualities in breast cancer cells. MDSC has been linked to cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…[12,31] The immunosuppressive roles of MDSCs are relatively well-understood in tumors. [12,31,34] It has been reported that MDSC enhances stem-like qualities in breast cancer cells. MDSC has been linked to cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory cells will be attracted to deal with the effect of pro-inflammatory innate immune cells (e.g., M1 macrophages and natural killer cells) and cytotoxic T cells. Tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) [53] enhance stemness and favor a pro-tumoral and pro-metastatic state by releasing cytokines (e.g., IL-6) that activate STAT3, ultimately inducing several stem-related pathways, EMT, and the expression of CSC markers, such as CD133 [54]. Underscoring the significance of the niche for the maintenance of CSCs, TAM depletion leads to a reduction in CSC numbers, tumor size and metastasis [55], while MDSC depletion increases the effect of cytotoxic T cells and reduces tumor growth [56].…”
Section: The Csc Niche the Tumor Microenvironment And Metastasismentioning
confidence: 99%
“…Although G‐MDSC and M‐MDSC could both impede T cell responses, the latter was more suppressive . Except for immunosuppressive effects on cancer development, more evidence showed that MDSC could accelerate the development of cancers by inducing autophagy, reprogramming metabolic status and supporting cancer cell stemness . It remains unclear whether RSV also modulated M‐MDSC in other cancer‐bearing mice models.…”
Section: Discussionmentioning
confidence: 99%
“…40 Except for immunosuppressive effects on cancer development, more evidence showed that MDSC could accelerate the development of cancers by inducing autophagy, reprogramming metabolic status and supporting cancer cell stemness. [41][42][43] It remains unclear whether RSV also modulated M-MDSC in other cancer-bearing mice models. Therefore, in future, we will consider the influence of RSV on M-MDSC in different cancer-bearing models.…”
Section: Discussionmentioning
confidence: 99%